Retrieval of aerosol microphysical parameters based on a few optical parameters from lidar. Issue 5 (25th December 2021) - Li, Siwen; Di, Huige; Zhang, Xingqi; Xin, Wenhui; Zeng, Nan; Ma, Hui; Li, Yan; Hua, Dengxin
Abstract: Aerosol optical parameters detected by multiwavelength lidar can be used for the retrieval of the aerosol particle size distribution and aerosol microphysical properties (AMP). Based on the retrieval for AMPs using standard principal component analysis (PCA) algorithm, the influence of the number of optical parameters on the PCA retrieval results is studied. Four optical parameters (3 β  +  α ) or three optical parameters (3 β ) are selected for retrieval instead of five optical parameters (3 β  + 2 α ), respectively. The results show that three optical parameters and four optical parameters can be used for the retrieval of AMPs. For 3 β  +  α, the accuracy of effective radius and volume concentration (VC) are 37% and 56%, respectively. For 3 β, the accuracy of effective radius and VC are 37% and 74% respectively. The sensitivity analysis of the PCA algorithm with less than five optical parameters is also discussed, and this method is applied to the retrieval of cloud base particle size distribution.